INCIDENCE OF ROOT (WILT) DISEASE IN VARIOUS CROSS COMBINATIONS OF WEST COAST TALL VARIETY OF COCONUT - R.V. Nair; P.M. Jacob; M.G. Rajesh; R.J. Thomas (International Coconut Community, 2003)
Root (wilt) disease is a very serious disease of coconut in eight southern districts of Kerala, India. A comprehensive breeding programme – the only practical solution for the management of the disease – was started at Central Plantation Crops Research Institute (CPCRI), Kayangulam during 1987. Coconut seedlings, belonging to five cross combinations with WCT viz. WCT (Inter se), West Coast Tall (WCT) (Self), WCT (Mixed Pollen), Chowghat Green Dwarf (CGD) x WCT and WCT (Open Pollinated) were studied for their incidence of root (wilt) disease. All the seedlings were planted during 1992 except CGD x WCT which was planted during 1991. In the absence of a mass screening technique under artificial conditions, assessment of resistance was based on natural infection. The progenies belonging to various cross combinations of WCT x WCT showed significant variability for incidence of root (wilt) disease. Observations, recorded during September 2002, revealed that the incidence of root (wilt) varied from 53.4 to 55.2 % in WCT x WCT crosses whereas CGD x WCT had 64.5 %. Open pollinated seedlings from healthy mother palms contracted 70 % incidence of the disease. The studies showed superiority of artificially pollinated seedlings (full sibs) over the open pollinated seedlings (half sibs) with regard to their susceptibility to the disease.